THE READINESS OF STUDENTS FOR CAREER SELF-MANAGEMENT - Katane, Irēna; Korna-Opincāne, Evita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Nowadays, several of the global challenges we are facing include the fast pace of life and rapidly occurring changes, therefore when interacting with this changeable life environment it is important for the young people to self-develop, self-manage, as well as be themselves in charge of their personal change and career management. This article studies the latest scientific trends, providing scientific justification to the student readiness for their career self-management. In the process of developing this justification, it was essential to understand the criteria and indicators for the student readiness for their career self-management, in order for the young people to be able to self-assess the said readiness during their entire lifetime. Therefore  the aim of the study was to develop the theoretical foundations for the term “student readiness for career self-management” within the context of general secondary education, including both criteria and indicators for the assessment which could in its turn become a methodological foundation for developing methodology for the readiness for career self-management. As a result of this study, the theoretical findings from the scientific literature on the essence and readiness for career self-management were gathered, examined, analysed, systemized and evaluated.